Numerical Techniques for the Analysis of Charge Transport and Electrodynamics in Graphene Nanoribbons - Luca Pierantoni; Davide Mencarelli (Nanomaterials and Nanotechnology)
In this paper, we report on multiphysics fullwave techniques in the frequency (energy)‐domain and the time‐domain, aimed at the investigation of the combined electromagnetic‐coherent transport problem in carbon based on nano‐structured materials and devices, e.g., graphene nanoribbons. The frequency‐domain approach is introduced in order to describe a Poisson/Schrödinger system in a quasi static framework. An example of the self‐consistent solution of laterally coupled graphene nanoribbons is shown. The time‐domain approach deals with the solution of the combined Maxwell/Schrödinger system of equations. The propagation of a charge wavepacket is reported, showing the effect of the self‐generated electromagnetic field that affects the dynamics of the charge wavepacket.